Improving Students' Basic Chemistry Competences Through Implementation of Class-Based Assessments in Inquiry-Based Chemistry Learning - Suherman Suherman (Universitas Pendidikan Mandalika, 2023)
This study aims to improve students' basic competencies in Chemistry subjects on Compound Polarity by implementing Authentic Assessment assessments in inquiry-based Chemistry learning. This type of research is classroom action research, which consists of two cycles. Each cycle consists of four stages: action plan, implementation, observation/evaluation, and reflection. This research was carried out in the 11th grade of science (IA) 2 class, state senior high school (SMAN) 2 Dompu involving 36 students in 2021. Data on students' cognitive competence are collected by the test method, data on students' affective competence are collected by observation method, and data on students' psychomotor competence are collected by observation method. Furthermore, the three data were analyzed descriptively. The findings of this study showed that (1) there was an increase in students' cognitive competence from an average score of 67.72 with classical learning completeness of 52.84% in cycle I to an average score of 77.60 with classical learning completeness of 87.29% in cycle II, (2) there was an increase in students' affective competence from an average score of 81.40 with a suitable category in cycle I to an average score of 86.80 with an excellent category in cycle II, and (3) there was an increase in students' psychomotor competence from an average score of 67.43 with good category in cycle I to an average score of 78.25 with good category in cycle II. Thus, it can be concluded that there is an increase in students' basic competencies in chemistry through the implementation of classroom-based assessment in inquiry learning.